2022
DOI: 10.3389/fpsyg.2022.803339
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Trauma and Cortisol Reactivity: An Investigation of the Role of Task Appraisals

Abstract: BackgroundChildhood adversity is linked to adverse health in adulthood. One posited mechanistic pathway is through physiological responses to acute stress. Childhood adversity has been previously related to both exaggerated and blunted physiological responses to acute stress, however, less is known about the psychological mechanisms which may contribute to patterns of physiological reactivity linked to childhood adversity.ObjectiveIn the current work, we investigated the role of challenge and threat stress app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 49 publications
0
0
0
Order By: Relevance
“…The initial plasma cortisol level measurements may act as a predictor for the development of complications and permanent infirmity in such cases and so the need for extra efforts for their proper management. This was supported by Counts et al,(2022) who stated that cortisol exaggerated responses are manifested by higher-than-average cortisol levels, which may result in delayed return to normal and development of complications. They also added that previous study suggested that extreme responses may put the person at a higher risk for adverse health outcomes such as persistent illnesses and early death due to biologic wears and tears on the systems of the body.…”
Section: Discussionmentioning
confidence: 87%
“…The initial plasma cortisol level measurements may act as a predictor for the development of complications and permanent infirmity in such cases and so the need for extra efforts for their proper management. This was supported by Counts et al,(2022) who stated that cortisol exaggerated responses are manifested by higher-than-average cortisol levels, which may result in delayed return to normal and development of complications. They also added that previous study suggested that extreme responses may put the person at a higher risk for adverse health outcomes such as persistent illnesses and early death due to biologic wears and tears on the systems of the body.…”
Section: Discussionmentioning
confidence: 87%